Digitizarea – proces indispensabil sistemului securităţii informaţionale și securităţii umane [Articol] - Cozonac, Renata (Tipografia Artpoligraf, 2021)
The modern development of information technologies leads to the need to protect information. In this article were elucidated important aspects of the security of informatics systems and information security, being at the same time argued the necessity of security of information systems, for ensuring human and informational safety.
DIGITIZATION - AN INDISPENSABLE PROCESS FOR THE SYSTEM OF INFORMATION SECURITY AND HUMAN SECURITY
Keywords: democrație digitală; informatizarea societății; digitizare